FORMULASI KEBIJAKAN PENETAPAN UPAH MINIMUM KOTA PEKANBARU TAHUN 2015 - Adawiyah, Robiatun; Ridwan, Muhammad (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
The background of this research with the wage policy is an important component in employment, ie as one element in the implementation of the employment relationship has a strategic role in the implementation of industrial relations. In industrial relations, government, employers and workers are interrelated. Normatively they have the same interest on the continuity of the company. Employers have an interest in the continuity of the company, due to his responsibilities as leader and orientation for profit in accordance with the capital invested. Workers have an interest in the company as a source of income and livelihood. While the government also has an interest in the continuity of the company with regard to economic growth both on a local and nasional.Perbedaan views on the establishment of wage levels often trigger disputes between workers and employers. Therefore, to reach agreement on the determination of wage rates and the role of government intervention need to be involved. Based on research carried out can be concluded that in setting the minimum wage figures cities (UMK) Pekanbaru in 2015, there are several considerations, namely the number KHL, productivity, economic growth, labor market conditions, business conditions are least able and the company's ability. Policy formulation is done at the start of the survey numbers KHL, discussion consideration of the proposal UMK, UMK submit a proposal to the Mayor and confirmed by the Governor in accordance with all applicable regulations.Keyword : policy formulation, the Minimum Wages City, Pekanbaru